AZD1222 (ChAdOx1 nCov-19): A Single-Dose biodistribution study in mice. Issue 2 (21st January 2022) - Stebbings, Richard; Armour, Gillian; Pettis, Vivian; Goodman, Joanne
Highlights: AZD1222 is safe and well tolerated following intramuscular administration in mice. Biodistribution of AZD1222 is largely confined to administration sites. No AZD1222 was detected in blood, brain, spinal cord or reproductive tissue. Low levels of AZD1222 were observed in sites of the reticuloendothelial system. Levels of AZD1222 decreased from Day 2 to Day 29, indicating clearance. Abstract: Biodistribution studies of adenovirus-based vaccines support their clinical development by evaluating their spread and persistence following in vivo administration. AZD1222 (ChAdox1 nCov-19) is a replication-deficient non-human adenovirus-vectored vaccine for coronavirus disease 2019. In this nonclinical study, the biodistribution of AZD1222 was assessed in mice for 29 days following intramuscular injection. Results show that AZD1222 was safe and well tolerated, with a spread that was largely confined to administration sites and the proximal sciatic nerve, with low levels observed in sites that are involved in rapid clearance of particulates by the reticuloendothelial system. Accordingly, levels of AZD1222 decreased from Day 2 to Day 29, indicating clearance. There were no quantifiable levels of AZD1222 in the blood, brain, spinal cord, and reproductive tissue, suggesting a lack of widespread or long-term distribution of AZD1222 vector DNA throughout the body following its administration.